Synthesis of N-Doped Few-Layer Graphene through Shock-Induced Carbon Fixation from CO2 - Hao Yin; Xin Gao; Jianjun Liu; Pengwan Chen (Nanomaterials, 2022)
In this study, graphene and N-doped graphene nanosheets were synthesized through the shock-induced reduction of CO2 using a cylindrical shock-loading apparatus. The mixture of solid CO2 and Mg powder was filled in the pre-cooled sample tube and then impacted by a shock-driven cylindrical flyer tube. The impact generated a shockwave that propagated into the mixed precursor, inducing a chemical reaction between CO2 and Mg at a high shock pressure and high shock temperature. The recovered black powders were characterized via various techniques, confirming the presences of few-layer graphene. The mechanism is carefully shown to be that CO2 was reduced by Mg to form few-layer graphene under shock-induced high pressure and high temperature. By adding carbamide as an N source, this synthetic route was also applied to synthesize N-doped graphene nanosheets. Moreover, the yield and mass of the graphene materials in this study are up to 40% and 0.5 g, respectively. This study showed an efficient and easy-to-scale-up route to prepare few-layer graphene and N-doped few-layer graphene through shock synthesis.